Notes on taxonomy and nomenclature of Pelexia pauciflora (Orchidaceae) - Engels, Mathias Erich; de Camargo Smidt, Eric (Acta Biológica Paranaense, 2025)
During the study of Microchilus (Goodyerinae, Orchidaceae) for Brazil, a problem regarding the systematic positioning of Pelexia pauciflora was identified. This name has historically been inconsistently placed, sometimes in the subtribe Spiranthinae and at other times in Goodyerinae. After examining the type materials and studying the protologues, we concluded that this taxon belongs to Spiranthinae, with Eltroplectris pauciflorus as the correct name to use. Furthermore, we discuss and propose the second-step of lectotypification for this name, along with the synonymization of Eltroplectris guimaraesii under E. pauciflorus.